Corrosion behavior of AA2024-T6 and AA6065-T6 alloys in reline. (10th October 2020) - Bucko, Mihael; Bastos, Alexandre C.; Yasakau, Kiryl A.; Ferreira, Mario G.S.; Bajat, Jelena B.
Highlights: AA2024-T6 and AA6065-T6 alloys are very stable in water free reline Passive film on Al alloys forms already after three hours of immersion in reline Passive films on Al alloys become more compact and thicker over time in reline Passive behavior of Al alloys in reline is due to very low solubility of oxide/hydroxide film There is no evidence of chemical bonding of passive film with organic species from reline Abstract: Deep eutectic solvents have been widely acknowledged as ionic liquid analogues, since they share many characteristics and properties with ionic liquids. The two major application areas of deep eutectic solvents have been metal processing and synthesis media; however, plenty of other applications have already been reported and predicted for these liquids. Reline, an eutectic mixture of choline chloride and urea, is a well known representative of deep eutectic solvents. Despite their importance in the contemporary technologies, the knowledge about the corrosivity of deep eutectic solvents is remarkably scarce. This article reports the results on the corrosivity of reline towards two Al alloys, namely AA2024-T6 and AA6065-T6. To measure the corrosion rates and characterize the passive film on the alloys in reline, electrochemical impedance and inductively coupled plasma optical emission spectroscopy methods were used, and the corrosion product composition was analyzed by X-ray photoelectron spectroscopy. Surface morphology and Volta potential were imaged by scanning electron microscopy, atomic force microscopy and scanning Kelvin probe force microscopy. The corrosion tests show that the two alloys are extremely stable in reline, and the passive layer is formed in the first three hours of immersion in the corrosive media. There is no evidence that electrolyte species are incorporated into the Al oxide protective layer through chemical bonding.